IMPLEMENTATION OF MULTI-SYSTEM SILVICULTURE (MSS) TO IMPROVE PERFORMANCE OF PRODUCTION FOREST MANAGEMENT: A CASE STUDY OF PT. SARPATIM, CENTRAL KALIMANTAN - Suryanto Suryanto; Adi Susilo; Onrizal Onrizal; M. Andriansyah; Teguh Muslim (Indonesian Journal of Forestry Research, 2018)
To date, performance of  the management of  Indonesian production forests are discouraging. The concession areas, timber production and employment have been decreasing over time. concern on these matter and to improve management, a research was conducted for six years (2008-2013) and resulted in recommendations to implement the Multi-System of Silviculture (MSS) systems. Two products were generated in MSS; criteria and indicator to guide the selection of  appropriate silvicultural system and supersilvik, a model to develop the best business plans. This paper evaluates  and strengthens the recommendations through the simulation of  MSS products in PT. Sarmiento Parakantja Timber (Sarpatim), Central Kalimantan, Indonesia. Various data variables were used, such as thematic maps of  forest areas, data of  stand, materials, equipments, labors, finances and incomes. Data were processed in a variety of  formulations which were connected to each other in model systems to produce a variety of  outcomes, such as production, finance, employment and tax contributions. Results offer four options to improve PT. Sarpatim performance, one of  which is the best choice. Compared to the former business model under limited silvicultural systems, MSS  projected an increase in the use of  land, timber production and employment by 151-753%. Implementing MSS will provide a better and healthier finance for company with an increase of  NPV up to 193%; as well as for government tax revenues with an increase up to 308%. This MSS case study strongly suggests using the new theory that the management of  production forests is a land and plant-based enterprises, which should put the land as the major capital and silvicultural aspects as the driving engine for production. The policy makers should be able to use these results as a reference in implementing MSS widely as part of  Sustainable Forest Management (SFM) practices.